Այգեգործությունը միջնադարյան Հայաստանում - Հ. Վ. Բեգլարյան (Հայկական ԽՍՀ գիտությունների ակադեմիա)
Садоводство являлось одним из самых распространенных видов сельскохозяйственной деятельности в средневековой Армении. Оно было развито не только в селах, но и в городах и поселках. Определенная часть населения средневекового города была занята обработкой и уходом за пригородными садами и огородами.Gardening was one of the most spread economic occupations in medieval Armenia. It developed not only in villages but also in settlements and towns. A certain part of the medieval town inhabitants engaged in the cultivation and care of suburban gardens and vegetable plots.
Keywords: History; Agriculture; Plant biology; Medieval History; D History